How coalitions shape legislative institutions in parliamentary democracies - Zubek, R (University of Chicago Press, 2024)
Previous work shows that robust legislative oversight institutions strengthen the ability of coalition governments to enforce policy agreements. This raises the question of whether coalitions choose such institutions strategically. In this article, I propose a simple formal model of procedural choice under coalition government and probe its empirical plausibility in a novel analysis of committee procedure reforms undertaken in 14 European parliamentary democracies over more than 60 years. The analysis reveals an empirical pattern which is broadly consistent with expectations. Procedural opportunities to use legislative committees to challenge ministerial proposals tend to be strengthened under multi-party cabinets in which preference divergence between coalition partners is substantial and in which parties have similar probability of making proposals to implement joint policies. These findings open interesting avenues for future work on how parties shape legislative institutions in parliamentary democracies.